Influence of hydraulic fracturing on impedance and efficiency of thermal recovery from HDR reservoirs. (September 2016) - AbuAisha, Murad; Loret, Benjamin
Abstract: Impedance and efficiency are key characteristics in regard to the economic viability of geothermal sites. The influence of hydraulic fracturing process on the efficiency of thermal recovery from HDR reservoirs is addressed in a totally coupled thermo-poroelastic framework. A fracturing model (HFM) is integrated into a domestic Fortran 90 finite element code. At any time and any geometrical point, the state of fracture is embodied in a fabric: the later includes both the actual fracture length and the actual fracture width in all directions of space. The local current anisotropic permeability tensor, which describes the evolving hydraulic connectivity of the fractured medium, is obtained by directional integration of the updated fracture fabric. A modified version of the model which accounts for the effect of deviatoric stresses on the fracturing criterion is shown to have stronger effects on the enhancement of the permeability. To gain confidence in the numerical approach, simulations are correlated to field data of the Soultz-sous-Forêts geothermal site that are available in the early times of the injection process. Cooling facilitates significantly the fracturing process close to the injection well. The model is next applied to simulate a hydraulic fracturing test over a long period of time. Hydraulic fracturing is shown to decrease the impedance of the reservoir, but it reduces the duration of an efficient exploitation. The nature of the mechanical, hydraulic and thermal boundary conditions is also investigated. The composition of the working fluid and the change of its viscosity with temperature are shown to affect fluid and heat transports in the poroelastic medium and hence the efficiency of hydraulic fracturing. Highlights: Hydraulic fracturing for heat recovery is studied in a thermo-poroelastic analysis. Two versions of a fracturing model are inserted into a domestic finite element code. Simulations are correlated to field data of Soultz-sous-Forêts geothermal site. The change of the viscosity of the working fluid with temperature is investigated. Effects of hydraulic fracturing on impedance and efficiency are emphasized.